70th EAGE Conference and Exhibition Incorporating SPE EUROPEC 2008 2008
DOI: 10.3997/2214-4609.20147940
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Velocity Model Building Using Iterative Eigendecomposition

Abstract: Tomographic velocity model building has become an industry standard for depth migration. However, regularizing tomography still remains a subjective virtue, if not black magic. Singular value decomposition (SVD) of a tomographic operator or, similarly, eigendecomposition of corresponding normal equations, are well known as a useful framework for analysis of most significant dependencies between model and data. However, application of this approach in velocity model building has been limited, primarily because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…As described in Osypov et al (2008b), we employ Lanczos iterations to perform eigendecomposition on the Fisher information operator of the data with respect to the model in the preconditioned space,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in Osypov et al (2008b), we employ Lanczos iterations to perform eigendecomposition on the Fisher information operator of the data with respect to the model in the preconditioned space,…”
Section: Methodsmentioning
confidence: 99%
“…Here, we judged our model good enough to stop because the final gammas were below 1% and the scale length was short enough. We perform the uncertainty analysis (Osypov et al, 2008b). Two set of a prior distribution were used, one from rock physics and displayed in Figure 1, the other is the relaxed prior used in control experiment in tomography as showed in figure 2 as red ellipse.…”
Section: Case Studymentioning
confidence: 99%
“…In this paper, we extend the work (Osypov et al, 2008) to VTI tomography, modify the process of regularization optimization, and propose an updated way for resolution and uncertainty quantification using the apparatus of eigendecomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines, Zhang and Thurber (2007) demonstrated that Lanczos iterations with random starting vector can overcome the above mentioned LSQR limitations in LSQR. Osypov et al (2008) applied a similar approach, to tomographic velocity model building as a modification of preconditioned regularized least-squares based on the truncated eigendecomposition of the Fisher information matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation